A new way to investigate the damping properties of NR/CIIR blends characterized by the rebound behaviors. (19th July 2022) - Shi, Xinghui; Yuan, Xiaojing; Guo, Xiaohui; Zeng, Fanqi; Liu, Guangyong
Abstract: In this work, effects of natural rubber (NR) content on the vulcanization and damping properties of chlorinated butyl rubber (CIIR) were studied. A new method to characterize the damping performance of the NR/CIIR blends by the rebound behavior of rubber ball was proposed. And an optical laser‐based measurement was used to follow the movement of the rubber sample. The DMA results showed that better damping properties of the blends was obtained at higher proportion of CIIR in the blends at room temperature (20°C) and a frequency of 0.1–100 Hz. Furthermore, a propose was made that the damping properties of the blends can be characterized by the rebound behavior of the rubber ball, and two methods were developed to characterize the damping properties of the blends according to the rebound experimental results of the rubber ball. The functional relationship between the height of the nth bounce of the rubber ball and NR content was obtained by experimental fitting. The damping index ( DI ) was defined by combining the parameters such as bounce height, bounce times and bounce time of the rubber ball. It was expected that this study could provide a new idea for the characterization and testing of viscoelastic damping materials.